2002
DOI: 10.1093/molehr/8.12.1087
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and expression of the human Factor In the Germline alpha (FIGLA) gene in ovarian follicles and oocytes

Abstract: The Factor In the Germline alpha (FIGalpha) transcription factor regulates expression of the zona pellucida proteins ZP1, ZP2 and ZP3 and is essential for folliculogenesis in the mouse. Using the published mouse Figla sequence, BLAST searches identified a human chromosome 2 BAC clone with high sequence identity. Using PCR primers derived from this clone, amplicons derived from ovarian follicles and mature oocytes revealed 100% identity with the appropriate human BAC clone, the expected homology with the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 16 publications
2
64
0
Order By: Relevance
“…Whereas germ cell numbers in Figla-null female mice are normal during mid-embryogenesis, primordial follicles are never properly formed and germ cells are lost shortly after birth, resulting in sterility (Soyal et al, 2000). Notably, a Figla ortholog was identified in the human genome (Huntriss et al, 2002) and later found to be highly expressed in the primordial follicles of human ovaries. Furthermore, higher Figla expression was correlated with primordial follicle development (Bayne et al, 2004), and loss of Figla was associated with premature ovarian failure in women (Tosh et al, 2015;Zhao et al, 2008).…”
Section: The Transcriptional Control Of Primordial Follicle Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas germ cell numbers in Figla-null female mice are normal during mid-embryogenesis, primordial follicles are never properly formed and germ cells are lost shortly after birth, resulting in sterility (Soyal et al, 2000). Notably, a Figla ortholog was identified in the human genome (Huntriss et al, 2002) and later found to be highly expressed in the primordial follicles of human ovaries. Furthermore, higher Figla expression was correlated with primordial follicle development (Bayne et al, 2004), and loss of Figla was associated with premature ovarian failure in women (Tosh et al, 2015;Zhao et al, 2008).…”
Section: The Transcriptional Control Of Primordial Follicle Developmentmentioning
confidence: 99%
“…As described in this Review, excessive follicle depletion often takes place very early in life and can result from genetic perturbations, altered hormonal signaling or environmental toxicants. Interestingly, many of the candidate factors identified in mice, including Nobox (Bouilly et al, 2015(Bouilly et al, , 2011Qin et al, 2007), Figla (Huntriss et al, 2002;Tosh et al, 2015;Zhao et al, 2008) and Taf4b (Di Pietro et al, 2008;Knauff et al, 2009), have since been implicated in POI in humans. Whereas a better understanding of ovarian reserve establishment and maintenance might not lead to therapies in all cases, knowledge of the causes of this condition can help prospective parents to make informed choices about their fertility options and the reproductive health of their daughters (Cordts et al, 2011;Nelson, 2009).…”
Section: Understanding Reproductive Senescence In Womenmentioning
confidence: 99%
“…Because it contains the primary sperm receptor (zona pellucida 3 [Zp3]) (44), its specificity and function made it an attractive target for immunocontraception research in the past. The mouse zona pellucida consists of three highly glycosylated proteins organized as Zp2-Zp3 fibrils noncovalently crosslinked by Zp1, with expression coordinated by the transcription factor FIGLA (factor in the germline α), which is also needed for establishing germ cells (45) and which is present in humans (46). Human oocytes possess a fourth zona protein, ZP4, which is only represented in mice as a truncated pseudogene (47).…”
Section: Growth and Differentiationmentioning
confidence: 99%
“…Note high similarity of FIGalpha proteins outside conserved residues within the bHLH domain and in the N-terminus. Zf, zebrafish (Danio rerio), this work; medaka, Orysias latipies (AAD38902; Kanamori, 2000); human, Homo sapiens (XP_292886; Huntriss et al, 2002); mouse, Mus musculus (NP_036143; Liang et al, 1997); fugu, Takifugu rubripes (scaffold 352, Pufferfish genome assembly 2, join 50546-50725, 51262-51431, 52397-52728); tetraodon, Tetraodon nigroviridis (Tetraodon genome assembly 6, FS_CONTIG_763_1, join 14041-13862, 13238-13052, 12933-12882, 12508-12347); Xl, Xenopus laevis (AW646029, BI477650, AW643447, BI448320); Xt, Siluriana tropicalis (AL886932); rainbow trout, Oncorhynchus mykiss (BX074063, BX074064, BX078575). B: FIGalpha proteins are conserved in vertebrates.…”
Section: Figalpha Is a Putative Regulator Of The Zpc Promotermentioning
confidence: 99%